Mechanism of Forming Low Resistivity in Shale Reservoirs - Jirong Xie; Jiahuan He; Keming Zhou; Zhijuan Tang; Manfei Chen; Tingting He; Mengwen Zou; Tao Luo; Nong Li; Li Wang (Geofluids)
In the oil and gas industry, traditional logging mostly deems that oil and gas reservoirs are characterized by high resistivity, whereas the water layer is often by low resistivity. However, a lot of exploration and development practices on shale gas reservoirs in Sichuan Basin, China, prove that it is hard to characterize a functional relation between resistivity and water saturation using the Archie equation. Therefore, to make clear the mechanism to form low resistivity in shale gas reservoirs, the matrix resistivity was calculated through the percolation network simulation based on pore structure characteristics and mineral compositional parameters. Moreover, the resistivity in low-resistivity laminations of shale was measured through the finite element simulation. In addition, the reasons for such low resistivity in shale were analyzed according to the resistivity-forming mechanism, and the effects of penetration degree, width, quantity, and spatial distribution of the laminations on the resistivity were worked out. Those may provide theoretical support for explaining the phenomenon of low-resistivity gas reservoirs.